Mechanical and physical properties of hybrid banana pseudostem/glass fibre reinforced polyester composites - Inai, Nor Hanifawati (2013)
Over the last decade, polymers reinforced with natural fibre composites have been getting an increase attention from the academic world and various industries. Development of composites using natural fibres in combination with moisture and corrosion resistant synthetic fibres is one technique to enhance the strength and stiffness as well as moisture resistance of the resulting hybrid fibre composites. The main objective of this study is to determine the mechanical and physical properties of a biohybrid composite which consist of banana pseudostem fibres and glass fibres. The specimen made of various fibre contents (10%, 20%, 30% and 40% by volume) of banana pseudostem and glass fibres were prepared. This research investigates the effect of fibre content on the mechanical and physical properties of hybrid banana pseudostem/glass fibre reinforced polyester composites. This study also presents a detailed investigation of the properties of hybrid composites over a range of glass fibre and banana fibre ratios. Composites having a different volume ratio of banana:glass such as 0:1, 2.5:7.5, 5:5, 7.5:2.5 and 1:0 were fabricated using a compression moulding technique. Mechanical tests such as tensile, flexural and impact test were carried out in accordance to ASTM D5083, ASTM D790 and ASTM D256 respectively. The moisture effect is an important aspect of this research, because natural fibres are very hydrophilic. This research indicates the variation of physical properties in these materials in response to water absorption. Composites were also analyzed by scanning electron microscopy (SEM) in order to study the morphological characteristic of composites fracture surfaces and microstructure. Based on the results, except for banana/polyester composites, it was found that the tensile and flexural properties of all composites increased with the gradual addition of 10 vol% fibre content. The highest mechanical properties have been obtained for 40% fibre filler of hybrid and non-hybrid composites. In the case of hybrid banana pseudostem/glass fibre composites, incorporation of 7.5 volume fraction of glass fibre gives the highest values of mechanical properties. In banana/polyester composites, as the banana fibre loading increases, the decrease in tensile and flexural properties is observed but these natural fibre composites show significant enhancement in elongation at break. The gradual addition of 10 vol% fibre loading to the unsaturated polyester matrix increased the impact strength of all composites. It is interesting to note that the tensile, flexural and impact properties significantly increased by the incorporation of small amount of glass fibre in banana fibre composites,showing positive hybrid effect. It is also observed that the water absorption tendency and thickness swelling of composites decrease by the process of hybridization. In conclusion, hybridization of banana pseudostem fibre with glass fibre had positive effect on the mechanical and physical properties of its composites.